ANALISIS PENDAPATAN WANITA PEDAGANG SAYUR MAYUR (STUDI KASUS DI PASAR ARENGKA PANAM) DI KOTA PEKANBARU - Yulian Artha; Evy Maharani; Ermi Tety (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Base of this survey is analysis the contribution income of women seller vegetables for their family and how to know what kinds of factor and interesting their foor increasing them income. The writer use method for the survey is direct connecting to fieldwith the women with the purposive sampling. The total number of market traders Arengka Panam is 380 merchants. Sampel taken by 10% of the sword of vegetables namely 380 women merchants (only vegetable merchant populasion) to choose and determine the field in accordance witha the kriteria . kriteria is a trader of vegetables woman has a husband and have a place to trade is settled. The files collected with sekunder and primer files. The analysis file used is method descreption with explain quantitative and qualitative. The formula used in this survey is the formula the income of women selling vegetables, amount total capitaland the contribution their income of selling vegetables. the result of survey showed that average their contribution raising them income 56 %, it mean that the contribution vendors to help improve household income is quite large, with yhe income to help make ends meet their household. Responden with experience ranging from 1 – 20 years of tradevegetables Keywords : Revenue, income contribution, women, Seller Vegetables,Total cost.